A qualitative analysis of a culturally adapted PCIT training for black and latine clinicians: creating communities for providers of autistic youth - Onovbiona, Harlee; Chavez, Felipa; Quetsch, Lauren; Scudder, Ashley (Frontiers in Child and Adolescent Psychiatry, 2025)
Parent-Child Interaction Therapy (PCIT) is a widely known evidenced-based treatment (EBT) that has been used with Latine, Black, and neurodiverse children to improve the parent-child relationship and reduce challenging behaviors. Although considerable efforts have been made to disseminate PCIT to the wider community, fewer strides have been made to reach Black and Latine families in underserved communities—especially for families with neurodiverse children. One method to bridge the service gap for Black and Latine families is to train Black and Latine clinicians who primarily serve Black and Latine communities. Thus, the current pilot utilized a qualitative design and the Ecological Validity Model to examine the clinical and cultural impact of a culturally infused PCIT training pilot, the Creating Communities Initiative, for Black and Latine mental health providers (N = 8)., Black and Latine clinicians highlighted several beneficial cultural adaptations (e.g., racially-ethnically matched community) and barriers (e.g., low caseloads) to training completion and competency development. Overall, the results of the culturally infused PCIT training pilot provide a useful template for future dissemination efforts of PCIT to culturally diverse providers and families.